MON-LB010 Cyclic Progesterone Therapy for Androgenic Polycystic Ovary Syndrome (PCOS) - A Systematic Review of the Literature - Shirin, Sonia (J Endocr Soc, 2020)
Women living with androgenic PCOS (WLWP) experience unpredictable oligomenorrhea(1) and are at increased risk for endometrial cancer(2). Oral micronized progesterone (OMP) given cyclically (14 days/cycle or 4 weeks, Cyclic OMP), in luteal phase doses(3) (300 mg at bedtime) as a “luteal phase replacement” therapy would be likely to effectively treat both. In addition, evidence suggests PCOS is causally related to rapid pulsing of GnRH and LH (4); OMP normalizes LH pulsatility if androgen levels are not elevated (4). Previous searches did not find progesterone therapy for PCOS (5). Our research question: Does the peer-reviewed literature provide evidence for prescribing cyclic progesterone therapy in PCOS? Literature search methods used Medline (Ovid) and PubMed for published articles. Our search terms were: “polycystic ovary syndrome”, “androgenic PCOS”, and, “micronized progesterone.” We sought publications with eligible women participants having androgenic PCOS, drug exposures (cyclic OMP, vaginal progesterone, and in varying doses and durations) and specific outcomes (biochemical or patient-reported data or both) in all languages. We excluded reviews and practice guidelines but searched bibliographies for missed citations. Results discovered 18 articles in combined Medline (n=6) and PubMed (12) searches. After excluding duplicates, articles on estradiol (E2) alone E2 with OMP therapy, five eligible articles remained. We read all in full detail. Progesterone therapy was beneficial for WLWP as, even in sub-therapeutic doses (<300 mg at bedtime) and in cycles of too short durations (<14 days), it decreased luteinizing hormone (LH) (6,7) and total testosterone (7) levels. Vaginal progesterone (200 mg, b.i.d for 2 to 12 weeks) added to letrozole ovulation induction increased the pregnancy rate from 0 to 21% (8). Although present data suggest Cyclic OMP withdrawal predictively causes flow, we found no evidence it improved women’s cycle-related experiences nor decreased acne and hirsutism. Women-reported data on Cyclic OMP for improving androgenic PCOS cycle regularity, daily experiences and risks for endometrial cancer are needed. Reference: (1)Azziz R Nat Rev Dis Primers 2016;2:16057. (2)Barry J Hum Reprod Update 2014; 20:748. (3)Simon J Fertil Steril 1993;60:26. (4)Blank S Hum Reprod Update 2006;12:351. (5)Teede H Clin Endocrinol (Oxf) 2018;89:251. (6)Livadas S Fertil Steril 2010;94:242. (7)Bagis T J Clin Endocr Met 2002;87:4536. (8)Montville C Fertil Steril. 2010;94:678.